Identification and expression analysis of capsaicin biosynthesis pathway genes at genome level in Capsicum chinense - Wei Zhang; Dan Wu; Liping Zhang; Chengzhi Zhao; Huangying Shu; Shanhan Cheng; Zhiwei Wang; Jie Zhu; Pingwu Liu (Biotechnology & Biotechnological Equipment, 2022)
AbstractCapsicum chinense is one of the best ingredients for making chili sauces and extracting capsaicin. In this study, we identified 59 genes associated with shikimic acid, phenylpropane, unsaturated fatty acids, phenylalanine, valine, leucine, isoleucine and other metabolic pathways based on pepper genome. In the present study, 58 of the 59 genes involved in capsaicin synthesis were found to be unevenly distributed on 11 chromosomes, and several genes with the same number of exons and high homology were found to be clustered in a duplication region of the chromosome. The promoter regions of these genes were predicted and analyzed, and multiple gene promoters were found to contain MYB binding sites, which provided a reference for the subsequent exploration of MYB target genes. At the same time, the expression levels of genes related to capsaicin synthesis were analyzed based on different transcriptomes, and it was found that these genes showed significant differences in different plant development stages and different tissues. The results of this study will be helpful to further study the synthesis mechanism of capsaicin in Capsicum chinense and the functional relationship between genes.